Sustainability beyond technology : philosophy, critique, and implications for human organization - Heikkurinen, Pasi; Ruuska, Toni (Oxford University Press, 2021)
"Current debates on sustainability are largely building on a problematic assumption that increasing technology use and advancement are a desired phenomenon, creating positive change in human organizations. This kind of techno-optimism prevails particularly in the discourses of ecological modernization and green growth, as well as in the attempts to design sustainable modes of production and consumption within growth-driven capitalism. This transdisciplinary book investigates the philosophical underpinnings of technology, presents a culturally sensitive critique to technology, and outlines feasible alternatives for sustainability beyond technology. By examining the conflicts and contradictions between technology and sustainability in human organization, the book develops a novel way to conceptualize, confront and change technology in the modern society. The book draws on a variety of scholarly disciplines, including humanities (philosophy and environmental history), social sciences (ecological economics, political economy and ecology) and natural sciences (geology and thermodynamics) to contribute to sustainability theory and policy"--
Keywords: teollisuus; johtaminen; kestävä kehitys; vihreä talous; ympäristön tila; ekologia; teknologia